2011
DOI: 10.1007/s00221-011-2963-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimality versus variability: effect of fatigue in multi-finger redundant tasks

Abstract: We used two methods to address two aspects of multi-finger synergies and their changes after fatigue of the index finger. Analytical inverse optimization (ANIO) was used to identify cost functions and corresponding spaces of optimal solutions over a broad range of task parameters. Analysis within the uncontrolled manifold (UCM) hypothesis was used to quantify co-variation of finger forces across repetitive trials that helped reduce variability of (stabilized) performance variables produced by all the fingers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…We expected the adaptations to fatigue to be consistent with our previous studies where both V UCM and V ORT increased in accurate force production tasks during fatigue with V UCM showing a larger increase (Park et al, 2012; Singh, SKM, Zatsiorsky, & Latash, 2010a; Singh et al, 2010b; Singh et al, 2012). Therefore, our second hypothesis was that indices of force stabilizing synergies would increase at both levels of the hierarchy.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We expected the adaptations to fatigue to be consistent with our previous studies where both V UCM and V ORT increased in accurate force production tasks during fatigue with V UCM showing a larger increase (Park et al, 2012; Singh, SKM, Zatsiorsky, & Latash, 2010a; Singh et al, 2010b; Singh et al, 2012). Therefore, our second hypothesis was that indices of force stabilizing synergies would increase at both levels of the hierarchy.…”
Section: Discussionsupporting
confidence: 86%
“…Some studies have shown that in motor tasks that involve a redundant set of elements, the goal-relevant features of performance are relatively preserved during fatigue (Gates & Dingwell, 2008; Huffenus, Amarantini, & Forestier, 2006). We have also shown this to be true in accurate force production tasks (Park, Singh, Zatsiorsky, & Latash, 2012; Singh et al, 2010b; Singh, Zatsiorsky, & Latash, 2012). In the current study, we investigated the effects of exercise-induced fatigue of a single digit on motor variability and digit coordination in a static prehension task.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Indeed, redundancy makes it possible to adapt movements to the main constraints, i.e., the objective of the task, and to the secondary environmental constraints, which include perturbations or parallel tasks cropping up as the movement is performed (Latash, 2012). This approach differentiates state variables characterising the system, such as joint angle or muscle activation, and performance variables that describe performance of the task, such as an exerted force or a trajectory of the final effector (Park et al, 2010(Park et al, , 2012. Some of the state variables significantly affect task performance and should be controlled, while others have little effect and can be more loosely constrained.…”
Section: Movement Variability and Motor Controlmentioning
confidence: 99%
“…For example, in a task that requires the use of the index and middle fingers to produce a sum force of 10 N, the interaction between the two fingers to maintain 10 N in real time is measured via within-trial analysis, while the various combinations of the two fingers during repeat performance of this task is measured via between-trial analysis. Precedent studies mostly studied synergy mechanisms through between-trial analysis (Shim et al, 2004;Park, Singh, Zatsiorsky, & Latash, 2012). However, according to Scholz & Schoner (1999), between-trial and within-trial motor analyses are analyzing other controlling capabilities of the CNS (Scholz & Schöner, 1999).…”
Section: Introductionmentioning
confidence: 99%